Estudo dos fatores influenciadores dos comportamentos de mobilização dos recursos humanos em um hospital universitário federal brasileiro - Pinto, Carlos Américo Barreira (2009)
The aim of this research was to examine the influence of HRM practices and the mediating role of the psychological conditions of support, trust, justice and empowerment in the mobilization employee’s behaviors of Hospital Universitário Walter Cantídio / Universidade Federal do Ceará (Fortaleza – CE). We considered HRM practices those linked to human resources competence development, evaluation and feedback on performance and information sharing. As mediating variables some psychological conditions, such perceived organizational support, psychological empowerment, trust in leadership and procedural justice. The study has descriptive-quantitative nature, using a structured questionnaire, not identified, with 93 (ninety-three) questions, carried through a random sample of 638 (six hundred and thirty-eight) hospital employees. It was applied descriptive statistics and exploratory factor analysis, using structural equation modeling and bootstrapping as multivariate estimation procedures for the analysis of causal relationships. The results revealed that the hypothesis concerning the direct influence of competence development practices was not confirmed, however, perceptions of organizational support and psychological empowerment had a positive effect on the behaviors, which shows a mediated influence of these practices. In contrast, the positive influence of perceptions on trust in leadership was not confirmed. The hypothesis of direct and positive influence of information sharing practices was confirmed at the same time the hypothesis of direct and positive influence of the assessment and feedback on performance practices had not been confirmed. However, the perception of procedural justice as a mediator in the information sharing practice, revealed no significant influence on behavior, but working as mediator in the assessment and feedback on performance practice it was fully confirmed. These results indicate that mobilizing HRM practices may stimulate the adoption of positive behaviors by the employees of HUWC / UFC, but, however, may not be sufficient to improve them, if not also implemented practices of justice, support, trust and empowerment, in which employees could develop feelings of deep emotional links to the institution and, consequently, improve relationships, motivation and collective performance.